PERKEMBANGAN HADITS NABAWI PADA MASA SAHABAT DAN TABI’IN - Anita Fajarwati; Ahmad Manshur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Prophetic Hadith is the second primary source of Islamic law after the Qur’an and plays a crucial role in Muslim life. Therefore, the preservation and transmission of Hadith in the early period of Islam became a major concern of the Companions of the Prophet and subsequent generations. This article aims to examine the development of Prophetic Hadith during the periods of the Companions and the Tabi’in, focusing on methods of preservation, challenges encountered, and their impact on the emergence of Hadith sciences. This study employs a literature review method by analyzing classical and contemporary works in the field of Hadith studies. The findings indicate that during the period of the Companions, Hadith was preserved primarily through memorization, limited written documentation, and a cautious approach to transmission. In the period of the Tabi’in, greater emphasis was placed on the chain of transmission (isnad), along with the emergence of narrator criticism in response to political and social challenges. Both generations played a fundamental role in safeguarding the authenticity of Hadith and establishing the methodological foundation for the subsequent codification of Hadith.